2019
DOI: 10.1007/978-1-4939-9488-5_19
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Analyses from Tissues in Parkinson’s Disease

Abstract: Metabolomics has been successfully applied to study neurological and neurodegenerative disorders including Parkinson’s disease for: 1) the identification of potential biomarkers of onset and disease progression; 2) the identification of novel mechanisms of disease progression; and 3) the assessment of treatment prognosis and outcome. Reproducible and efficient extraction of metabolites is imperative to the success of any metabolomics investigation. Unlike other OMICS techniques, the composition of the metabolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…One-dimensional (1D) 1 H NMR data collection and analysis were completed as described previously ( 40 42 , 67 69 ). Briefly, samples from each class were prepared for NMR analysis by dissolving the lyophilized culture medium into 600 μl of 50 mM phosphate buffer (pH 7.2, uncorrected) in 99.8% D 2 O with 50 μM 3-(tetramethylsilane)propionic acid-2,2,3,3-d4 (TMSP).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One-dimensional (1D) 1 H NMR data collection and analysis were completed as described previously ( 40 42 , 67 69 ). Briefly, samples from each class were prepared for NMR analysis by dissolving the lyophilized culture medium into 600 μl of 50 mM phosphate buffer (pH 7.2, uncorrected) in 99.8% D 2 O with 50 μM 3-(tetramethylsilane)propionic acid-2,2,3,3-d4 (TMSP).…”
Section: Methodsmentioning
confidence: 99%
“…These original data were obtained using liquid chromatography technology, but since then, our ability to collect high-resolution untargeted one-dimensional proton nuclear magnetic resonance (1D 1 H NMR) data and the statistical methods to deconvolute complicated spectra has evolved considerably, making untargeted NMR metabolomics of B. theta cultures feasible ( 40 42 ). Our study aimed to use untargeted metabolomics, systems biology, and biological modeling techniques to revisit the metabolism of this important human symbiont to account for nutrient inputs and outputs and to gain insight into how B. theta responds to physiological concentrations of metabolic fermentation products that are encountered in the gut ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafiltration has also been utilized, but may result in significant metabolite loss due to macromolecule binding, and should be used with caution when accurate quantification is desired [42,43]. Tissue samples are also commonly analyzed by solution state NMR, but must be homogenized prior to metabolite extraction [44]. Prior to sample storage, the effective concentration of biofluid samples may be improved by drying the sample and then, reconstituting in a phosphate buffer to the desired sample volume [44].…”
Section: Sample Storage and Preparation For Metabolomics Analysismentioning
confidence: 99%
“…Tissue samples are also commonly analyzed by solution state NMR, but must be homogenized prior to metabolite extraction [44]. Prior to sample storage, the effective concentration of biofluid samples may be improved by drying the sample and then, reconstituting in a phosphate buffer to the desired sample volume [44]. This is particularly useful when a limited sample is available for NMR analysis, but it does require extra preparation time and may perturb the sample leading to erroneous quantification.…”
Section: Sample Storage and Preparation For Metabolomics Analysismentioning
confidence: 99%
“…Similarly, metabolic profiles of blood in idiopathic PD are also different from healthy groups, such as alpha-synuclein, tau protein, urate, and a series of amino acid metabolism ( Bolner et al, 2011 ; Luan et al, 2015 ; Saiki et al, 2017 ; Chang et al, 2018 ; Goldman et al, 2018 ). These disturbances in the metabolic pathways are related to mitochondrial dysfunctions and the concomitant changes in energy homeostasis and redox reaction, which are thought to be the final common pathways of most endogenous and exogenous factors that are involved in the etiology of PD ( Bhinderwala et al, 2019 ). Recent studies have revealed that there are metabolic differences between treated and drug-naïve PD patients ( Bogdanov et al, 2008 ; Troisi et al, 2019 ), as well as patients with and without dementia or depression ( Hatano et al, 2016 ; Dong et al, 2018 ).…”
Section: Metabolomicsmentioning
confidence: 99%